Human-related problems in quality management implementation in building construction projects - Tan, Chin Keng; Abdul Rahman, Hamzah (2009)
The research explores the human-related problems encountered in the implementation of quality management in building construction projects in the context of Malaysian construction industry. Survey samples were drawn from the construction organizations of G5, G6, and G7 registered with the Construction Industry Development Board (CIDB) Malaysia. Research findings indicate that the major human-related problems in the implementation of quality management in construction projects include human resources limitation, awareness of construction workers on the quality system is low and implementation of the quality system is not in full scale.